How to Constitute a Field of Merit: Structure and Flexibility in a Tibetan Buddhist Monastery's Curriculum - Townsend, Dominique (Religions, 2017)
The written curriculum of Tibet's prestigious Mindrölling monastery, composed in 1689, marries a firm pedagogical structure with flexibility for individual students. This reflects the monastery's balance of institutional priorities, shaped by its religious, cultural, and political climate. The curriculum's author was Terdak Lingpa, a charismatic visionary and systematizer of the Ancient or Nyingma school of Tibetan Buddhism who forged alliances with the Fifth Dalai Lama's government in Lhasa starting in the seventeenth century. As part of Mindrölling's formal constitutional document, the curriculum commits students and teachers to a distinctive approach to Buddhist training and helps to constitute the monastery and its members as a Buddhist field of merit. As such, Mindrölling is presented as a worthy recipient of support and protection from patrons and of respect from the community. The curriculum reflects a variety of overarching priorities for a relatively diverse student body over time and therefore calls for individual flexibility within a reliable and sustainable institutional structure. In this way, the curriculum demonstrates Mindrölling's identity as a bridge between the potentially competing values of the Tibetan Buddhist schools of the author's day.